Technetium-99m-based Radiopharmaceuticals in Sentinel Lymph Node Biopsy: Gynecologic Oncology Perspective - Zalewski, Kamil; Benke, Malgorzata; Mirocha, Bartlomiej; Radziszewski, Jakub; Chechlinska, Magdalena; Kowalewska, Magdalena (Current Pharmaceutical Design, 2018)
Technetium (99mTc)-radiolabeled colloids are popular tracers used to map lymphatic vessels and regional lymph nodes (LNs). The regional LN status is a significant determinant of cancer stage and patient prognosis, and strongly influences treatment. Regional LN dissection has become a part of surgical treatment. However, not all patients with LN involvement benefit from extensive lymphadenectomy in terms of prolonged survival. Moreover, overtreatment of patients with localized disease carries the unnecessary risk of complications. It is believed that sentinel LN biopsy (SLNB) allows to assess the involvement of the most representative LN of the lymphatic basin and to decide on radical LN dissection.99mTc is an easily available radionuclide emitting gamma rays. The value of 99mTc for diagnostic procedures is associated with its relatively short half-life that makes it safe both for patients and medical personnel. A colloid presenting specific physical and biological properties, including optimal particle size, is a carrier for the radionuclide. When administered at the tumor site, a radiocolloid is absorbed by the lymphatics, and the first LN that it gets trapped in is referred to as the sentinel LN (SLN). The radiopharmaceutical must reach the SLN relatively quickly, but its storage within the SLN, and the radionuclide's half-life must be long enough to enable intraoperative imaging and evaluation. SLNB is currently the gold standard in breast cancer and malignant melanoma diagnosis, and is under extensive investigation in gynecological cancers. Here, we provide a historical perspective of the SLN concept and the clinical relevance of SLNB in gynecologic oncology. Moreover, we review the technical aspects of the application of 99mTc-based radiopharmaceuticals in lymphoscintigraphy and intraoperative lymphatic mapping.
Keywords: 99mTc